Description of Tuber malenconii mycorrhizae and a comparison with mycorrhizae of T. aestivum and T. mesentericum - Garcia-Montero, Luis G.; Di Massimo, Gabriella; Manjon, Jose L.; Velazquez, Javier (MYCOTAXON, 2008)
Tuber malenconii is a recently described uncommon European truffle associated with Quercus ilex that is potentially detrimental to the cultivation of the highly prized edible, T. melanosporum. Examination of T. malenconii mycorrhizae synthesized from fresh ascocarps revealed polygonal mantle cells and numerous cystidia with basal-forked ramifications. Differences between T. malenconii, T. mesentericum, and T. aestivum mycorrhizae are noted; compound and scanning electron micrographs provide additional comparisons.
The following values have no corresponding Zotero field: pub-location: PO BOX 264, ITHACA, NY 14851-0264 USA publisher: MYCOTAXON LTD
Keywords: Ectomycorrhizae; hypogeous fungus; Tuberaceae